Association of two BRM promoter polymorphisms and smoking status with malignant pleural mesothelioma risk and prognosis. Issue 11 (29th July 2019) - Lee, Min Joon; Kuehne, Nathan; Hueniken, Katrina; Liang, Shermi; Rai, Sudhir; Sorotsky, Hadas; Herman, Michael; Shepshelovich, Daniel; Bruce, Jeffrey; Liang, Mindy; Patel, Devalben; Cheng, Dangxiao; et al.
Abstract: Brahma (BRM), of the SWI/SNF complex, has two 6 to 7 bp insertion promoter polymorphisms ( BRM‐741/BRM‐1321 ) that cause epigenetic BRM suppression, and are associated with risk of multiple cancers. BRM polymorphisms were genotyped in malignant pleural mesothelioma (MPM) cases and asbestos‐exposed controls. Multivariable logistic regression (risk) and Cox regression (prognosis) were performed, including stratified analyses by smoking status to investigate the effect of polymorphisms on MPM risk and prognosis. Although there was no significant association overall between BRM‐741/BRM‐1321 and risk in patients with MPM, a differential effect by smoking status was observed ( P ‐interaction < .001), where homozygous variants were protective (aOR of 0.18‐0.28) in ever smokers, while never smokers had increased risk when carrying homozygous variants (aOR of 2.7‐4.4). While there was no association between BRM polymorphisms and OS in ever‐smokers, the aHR of carrying homozygous‐variants of BRM‐741, BRM‐1321 or both were 4.0 to 8.6 in never‐smokers when compared to wild‐type carriers. Mechanistically, lower mRNA expression of BRM was associated with poorer general cancer prognosis. Electrophoretic mobility shift assays and chromatin immunoprecipitation experiments (ChIP) revealed high BRM insertion variant homology to MEF2 regulatory binding sites. ChIP experimentation confirmed MEF2 binding only occurs in the presence of insertion variants. DNA‐affinity purification assays revealed YWHA scaffold proteins as vital to BRM mRNA expression. Never‐smokers who carry BRM homozygous variants have an increased chance of developing MPM, which results in worse prognosis. In contrast, in ever‐smokers, there may be a protective effect, with no difference in overall survival. Mechanisms for the interaction between BRM and smoking require further study.